Energy parameters of ultrafine grinding of pharmaceutical and cosmetic ingredients in the bead mill - Hrininh-Hera, Kateryna; Gubenia, Oleksii (My University, 2020)
The energy parameters of the grinding process of the components of pharmaceutical and cosmetic preparations in a bead mill are considered. The purpose of research - to determine the energy parameters of ultrafine grinding of pharmaceutical and cosmetic ingredients in the bead mill. A series of experimenters was conducted where the degree of grinding was measured using USB Digital Microscope and software, the temperature was measured with a TPM-10 electronic thermometer, and the power was measured with a CNFAJ Intelligent Power Meter three-phase wattmeter. As a result of the study, we can conclude that most of the energy is spent on the work of mixing the beadproduct system and the work spent on heating the structural components of the product and the interacting parts of the mill, which, in turn, depend on the rheological properties of the suspension.
Keywords: grinding; beads; suspension; суспензія; надтонке подрібнення; бісерний млин; кафедра машин і апаратів харчових та фармацевтичних виробництв